Accumulation of p53 protein is frequent in ovarian cancers associated with BRCA1 and BRCA2 germline mutations. Issue 5 (1st May 1999) - Zweemer, R P; Shaw, P A; Verheijen, R M; Ryan, A; Berchuck, A; Ponder, B A; Risch, H; McLaughlin, J R; Narod, S A; Menko, F H; Kenemans, P; Jacobs, I J
Abstract : BACKGROUND: Mutations in the BRCA1 or BRCA2 genes are responsible for up to 95% of hereditary ovarian cancer cases. Both genes function as tumour suppressor genes, and development of a cancer is thought to require an accumulation of somatic genetic events in addition to the inherited germline predisposition. It is unknown whether these somatic events in BRCA associated ovarian cancer are similar to or distinct from those in sporadic cases. The most frequent somatic genetic event in ovarian cancer is a mutation of the p53 gene. AIM: To study the role of p53 in hereditary ovarian cancer, by analysing accumulation of the p53 protein in ovarian cancers which occurred in BRCA1 or BRCA2 germline mutation carriers and comparing the results with a panel of ovarian cancers from patients who tested negative for both BRCA1 and BRCA2. METHODS: The study group consisted of 39 ovarian cancer patients in whom a BRCA mutation had been confirmed previously. p53 Immunohistochemistry was performed on archival tissue using a standard microwave antigen retrieval technique. The rate of p53 accumulation was compared with 40 ovarian cancer cases who tested negative for BRCA1 and BRCA2 germline mutations. RESULTS: P53 Accumulation was similar in BRCA related ovarian cancers and BRCA negative controls. Overall 27 of 39 BRCA1 or BRCA2 positive cases (69%) had evidence of p53 accumulation, compared with 24 of 40 invasive ovarian cancer cases (60%) which tested negative for BRCA1 and BRCA2 germline mutations. BRCA1 related ovarian cancers showed p53 accumulation in 22 of 30 cases (73%); p53 accumulation was present in five of nine BRCA2 related ovarian cancers. CONCLUSIONS: In addition to germline BRCA1 and BRCA2 mutations, somatic p53 alterations leading to p53 accumulation are an important event in hereditary ovarian cancer and are as frequent as in non-BRCA-related ovarian cancer.